Additive Manufacturing: Materials, Processing, Characterization and Applications - Pan Wang; Takayoshi Nakano; Jiaming Bai (Crystals, 2022)
The current Special Issue collected 19 original articles reporting the results of theoretical and experimental studies that provide new insights into this fascinating new generation manufacturing process, additive manufacturing (AM) [...]